2010
DOI: 10.1075/aila.23.02roe
|View full text |Cite
|
Sign up to set email alerts
|

Explicit knowledge and learning in SLA

Abstract: SLA researchers agree that explicit knowledge and learning play an important role in adult L2 development. In the field of cognitive linguistics, it has been proposed that implicit and explicit knowledge differ in terms of their internal category structure and the processing mechanisms that operate on their representation in the human mind. It has been hypothesized that linguistic constructions which are captured easily by metalinguistic descriptions can be learned successfully through explicit processes, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The pastcounterfactual conditional is a complex and salient feature (Izumi et al, 1999). Roehr (2008Roehr ( , 2010 suggested that difficulty with learning grammatical rules explicitly varies based on the schematicity, conceptual complexity, technicality, truth value, stability, and context independency of grammatical structures. Explicit instruction on features with different difficulties might thus result in different outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The pastcounterfactual conditional is a complex and salient feature (Izumi et al, 1999). Roehr (2008Roehr ( , 2010 suggested that difficulty with learning grammatical rules explicitly varies based on the schematicity, conceptual complexity, technicality, truth value, stability, and context independency of grammatical structures. Explicit instruction on features with different difficulties might thus result in different outcomes.…”
Section: Resultsmentioning
confidence: 99%